2021
DOI: 10.1590/1980-220x-reeusp-2020-0238
|View full text |Cite
|
Sign up to set email alerts
|

Board Game Violetas: the perspective of professionals addressing violence against women

Abstract: Objective: To analyze the potentialities and limits of the board game Violetas to address violence against women, from the perspective of the professionals who work in assisting the victims. Method: This is an interventional study with a qualitative approach. Thirty professionals from the Casas da Mulher Brasileira (Brazilian Women’s Houses) in Brasília, Campo Grande and Curitiba participated. Data collection was carried out during Critical-Emancipatory Workshops. Data were subjected to thematic content analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…This study is a continuation of previous research that identified the potential of “ Violetas ” for the expansion of critical awareness about gender violence with professionals who worked in the intersectoral network. In addition to this, revealed the need for educational intervention (EI) to complement the discussions raised at the start, to deepen the understanding of the problem and the perspective of its coping ( 10 ) . This data was supported by another Brazilian research, which considered the game as a mediating tool in the learning process, because, in addition to encouraging dialogue and the exercise of critical analysis, it depends on the intentionality of those involved ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…This study is a continuation of previous research that identified the potential of “ Violetas ” for the expansion of critical awareness about gender violence with professionals who worked in the intersectoral network. In addition to this, revealed the need for educational intervention (EI) to complement the discussions raised at the start, to deepen the understanding of the problem and the perspective of its coping ( 10 ) . This data was supported by another Brazilian research, which considered the game as a mediating tool in the learning process, because, in addition to encouraging dialogue and the exercise of critical analysis, it depends on the intentionality of those involved ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Este estudo é continuidade de pesquisa anterior que identificou as potencialidades do jogo "Violetas" para a ampliação da consciência crítica sobre a violência de gênero com profissionais que atuavam na rede intersetorial. Além disso, revelou a necessidade de intervenção educativa (IE) complementar as discussões levantadas na partida, para o aprofundamento da compreensão do problema e a perspectivação do seu enfrentamento (10) . Esse dado foi corroborado por outra pesquisa brasileira, que considerou o jogo como ferramenta mediadora do processo de aprendizagem, pois, além de estimular o diálogo e o exercício da análise crítica, depende da intencionalidade dos envolvidos (11) .…”
Section: Introductionunclassified